Penyalahgunaan Posisi Dominan Oleh Pelaku Usaha Dominan Melalui Penggunaan Algoritma Harga - Ria Setyawati; Rayhan Adhi Pradana (UIR Law Review, 2022)
Advancement of technology resulted in a digitalized business world. Consequently, businesses start to use technology like algorithms to make business decisions, for example, introducing algorithms to set prices. Such algorithms are known as pricing algorithms. However, when these algorithms are utilized by a dominant firm, it exposes a risk of abuse. There is also a concern relating to available legal recourse by competition authorities in tackling this novel issue. Thus, this research aims to analyse the relationship between algorithmic pricing and abuse of dominant position, as well as providing solutions pertaining to available legal recourse that might be useful for competition authorities in facing this contemporary issue. To this end, this legal research employs statute, conceptual, case, and comparative approaches. Through these methodologies, this research analyses the usage of algorithmic pricing and abuse of dominant position in conformity to Indonesian law; and transforming the available legal recourse to be more accommodative in confronting the use of algorithmic pricing.The use of algorithmic pricing can entail an abuse of dominant position, considering the ability of algorithms to impose trade restrictions, hence excluding potential competitors and preventing consumers from attaining a fair price. Available legal recourse that can be considered by competition authorities are: increasing knowledge on algorithmic pricing, imposing regulations to support transparency and accountability, and using a structural approach. In terms of evidence, authorities should put more weigh on digital evidence, circumstantial evidence, and expert opinions.